2014
DOI: 10.1111/imm.12299
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 is essential for lipopolysaccharide‐dependent activation of human intestinal mast cells from macroscopically normal as well as Crohn's disease tissue

Abstract: SummaryMast cells are now considered sentinels in immunity. Given their location underneath the gastrointestinal barrier, mast cells are entrusted with the task of tolerating commensal microorganisms and eliminating potential pathogens in the gut microbiota. The aim of our study was to analyse the responsiveness of mast cells isolated from macroscopically normal and Crohn's disease-affected intestine to lipopolysaccharide (LPS). To determine the LPS-mediated signalling, human intestinal mast cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…45 Serumderived soluble CD14 may compensate for this effect. 46 Various studies, including ours, have demonstrated that MCs express all components of the NLRP3 inflammasome. Priming of MCs with LPS further enhances the expression of NLRP3.…”
Section: Mast Cells As Producers Of Il-1βmentioning
confidence: 82%
See 1 more Smart Citation
“…45 Serumderived soluble CD14 may compensate for this effect. 46 Various studies, including ours, have demonstrated that MCs express all components of the NLRP3 inflammasome. Priming of MCs with LPS further enhances the expression of NLRP3.…”
Section: Mast Cells As Producers Of Il-1βmentioning
confidence: 82%
“…On the other hand, it is also important for the recognition of the prototype TLR4 ligand LPS and endogenous TLR4 ligands . Serum‐derived soluble CD14 may compensate for this effect . However, in vitro, under serum free conditions, mouse BMMCs or peritoneal MCs (PMCs) are significantly less sensitive to TLR4 stimulation with LPS (smooth and rough variants) than bone marrow‐derived or peritoneal macrophages (J. Scheffel, unpublished data).…”
Section: Are Mast Cells Drivers Of Autoinflammation?mentioning
confidence: 99%
“…Because MMCs are distributed in the lamina propria, it seemed unlikely that MMCs directly sense the fatty acids in the intestinal lumen. However, intestinal MMCs are well documented to contribute to colitis, secretory diarrhea, and food allergies, which reflects on the ability of MMCs to detect allergens or harmful bacterial products 44,45 through receptor interactions, such as complement receptor 3, 46,47 CD48, 48 soluble CD14, 13 and Toll-like receptors. 4951 Activated MMCs in these pathological states impair the intestinal barrier 5256 and increase permeability, which enhances the flux of bacterial products or food antigens into the intestinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Fat absorption facilitates the absorption of bacterial lipopolysaccharide (LPS) from the gut, 7,11 which associates with chylomicron remnants. 12 Because intestinal MMCs are activated by bacterial products, such as LPS 13 or Escherichia coli hemolysin, 14 we hypothesized that the gut microbiota is responsible for the lipid-induced activation of intestinal MMCs.…”
mentioning
confidence: 99%
“…98 Intriguingly, BMMCs and human intestinal MCs lack mCD14, with the consequence that they recognize R-chemotypes of LPS but not S-chemotypes. 99,100 In correlation, macrophages deficient in CD14 show an LPS recognition phenotype comparable with MCs. 101 Moreover, both murine BMMCs and murine peritoneal mast cells (PMCs) were found to lack the adaptor protein TRIFrelated adapter molecule, resulting in their inability to activate the TRIF pathway and hence to produce type I interferons on LPS stimulation.…”
Section: Innate Immune Receptorsmentioning
confidence: 96%